(untitled) (Journal of Economic Research & Business Administration, 2015)
The development of regions in developed countries shows that local governments play an important role is addressing social and economic problems. Consequently it is necessary to assign them more rights and powers and to reduce their dependence on the center. Another problem in domestic economy is the need to increase the efficiency of local budgets. The article analyses the revenues and expenditures of Akmola oblast budget for the last several years. On the basis of comparison of data the article identifies some problem issues of the oblast budget formation and looks at various areas of expenditures. Thus, as budget revenues increase there also increases funding for various priority programs. As a result of the analysis the author develops recommendations on ways to improve the efficiency of budget programs